(untitled) - Kim, W. Chan (Boston, Massachusetts, 2017)
Red Ocean Traps shows that managers' mental models--ingrained assumptions about the way the world works--undermine attempts to make market-creating strategic moves that unlock blue oceans. Kim and Mauborgne provide a framework that reveals the assumptions managers make in creating new markets that keep their efforts tethered to existing overcrowded industries (red oceans).
Keywords: Lãnh đạo,Leadership